Double duty actions to tackle all forms of malnutrition (P10-053-19) - Ruel, Marie T.; Hawkes, Corinna (Oxford University Press, 2019)
Most countries are now experiencing a double burden of malnutrition (DBM), characterized by the coexistence of nutritional deficiencies (underweight, wasting, stunting, micronutrient deficiencies) and overweight/obesity and diet-related non-communicable diseases (obesity/DR-NCDs). Actions to address the two sides of the DBM are typically managed by separate communities, policies, programs, governance structures, and funding streams. Double duty actions, defined as actions that simultaneously address nutritional deficiencies and obesity/DR-NCDs, have been proposed as a win-win solution to tackling malnutrition in all its forms. The objective of the work was to explore opportunities—and make recommendations—for double duty actions to be delivered by programs and policies in key sectors such as health, social protection, education, and agriculture.